Bioleaching of sand by the fungus fusarium oxysporum as a means of producing extracellular silica nanoparticles - Bansal, Vipul; Sanyal, A.; Rautaray, D.; Ahmad, Absar; Sastry, Murali (Advanced Materials, 2005)
A plant pathogenic fungus, Fusarium oxysporum, can be used as a biological model system for the extracellular bioleaching of hollow spherical silica nanoparticles (see Figure) from sand. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential waste materials could lead to eco-friendly and economically viable methods for the large-scale synthesis of nanomaterials.

Biological synthesis of stable vaterite crystals by the reaction of calcium ions with germinating chickpea seeds - Rautaray, D.; Sanyal, A.; Bharde, Atul A.; Ahmad, Absar; Sastry, M. (Crystal Growth & Design, 2005)
The total biological synthesis of CaCO3 crystals of the metastable vaterite polymorph at room temperature by simple protein-mediated reaction of aqueous Ca2+ ions with the CO2 generated during the root growth from germinating chickpea (Cicer arietinum) seeds is described. Highly stable vaterite crystals of spherical morphology are obtained, indicating that the proteins secreted from the roots during growth play a crucial role in stabilizing and directing the crystal growth.

Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation

Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Biotechnology of endophytic fungi: inorganic nanomaterials and drugs - Ahmad, Absar (Medicinal Chemistry Research, 2010)

Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver

Biotransformation of vinblastine to vincristine by the endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Ahmad, Absar (Biocatalysis and Biotransformation, 2013)
A fungal transformation method for the production of the less abundant but more valuable anticancer drug vincristine using the more abundant anticancer drug vinblastine by an endophytic fungus Fusarium oxysporum isolated from the plant Catharanthus roseus is described. Vinblastine dissolved in sterile water when incubated with the fungal mycelial mass was transformed into vincristine at room temperature. The biotransformation process was monitored by periodic sampling of aliquots that were extracted with ethyl acetate. The crude transformed compounds were analysed using TLC where the Rf value of the spot obtained on the 8th day was found to be similar to that of standard vincristine (Rf 0.74). Purification by HPLC using a C 18 symmetry column showed a peak with RT (34.9 min) similar to that of standard vincristine. Further characterization with the help of ESI-MS showed a peak at m/z 825 attributed to the (M + H)(+) ion. This indicated that the fungus Fusarium oxysporum had converted vinblastine to vincristine.
Keywords: Biotransformation; endophytes; fusarium oxysporum; Vinblastine; vincristine

Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Biosynthesis of fluorescent Bi2S3 nanoparticles and their application as dual-functionSPECT-CT probe for animal imaging - Uddin, Imran; Ahmad, Absar; Siddiqui, Ejaz Ahmad; Rahaman, Sk. Hasanur; Gambhir, Sanjay (Current Topics In Medicinal Chemistry, 2016)
Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that these may find use in animal imaging, diagnostics, cell labeling and other biomedical applications. Herein, we for the first time have biosynthesized highly fluorescent, natural protein capped Bi2S3 nanoparticles by subjecting the fungus Fusarium oxysporum to bismuth nitrate pentahydrate [Bi(NO3)(3).5H(2)O] alongwith sodium sulphite (Na2SO3) as precursor salts under ambient conditions of temperature, pressure and pH. The nanoparticles were completely characterized using recognized standard techniques. These natural protein capped Bi2S3 nanoparticles are quasi-spherical in shape with an average particle size of 15 nm, maintain long term stability and show semiconductor behavior having blue shift with a band gap of 3.04 eV. Semiconductor nanocrystals are fundamentally much more fluorescent than the toxic fluorescent chemical compounds (fluorophores) which are presently largely employed in imaging, immunohistochemistry, biochemistry, etc. Biologically fabricated fluorescent nanoparticles may replace organic fluorophores and aid in rapid development of biomedical nanotechnology. Thus, biodistribution study of the so-formed Bi2S3 nanoparticles in male Sprague Dawley rats was done by radiolabelling with Technitium-99m (Tc-99m) and clearance time from blood was calculated. The nanoparticles were then employed in SPECT-CT probe for animal imaging where these imparted iodine equivalent contrast.

Biological synthesis of alpha-Ag2S composite nanoparticles using the fungus Humicola sp. and its biomedical applications - Syed, Asad; Saedi, Marzouq Hussain Al; Bahkali, Ali H.; Elgorban, Abdallah M.; Kharat, Maheshkumar; Pai, Kalpana; Ghodake, Gajanan; Ahmad, Absar (Journal of Drug Delivery Science and Technology, 2021)
Synthesis of alpha-Ag2S (silver sulfide) is a highly challenging task, usually attempted using synthetic, hazardous chemical processes. This report puts efforts to exploring microbial-based eco-friendly alternatives. A facile, onepot biological method for the synthesis of alpha-Ag2S composite nanoparticles (NPs) in an aqueous medium at ambient conditions was established. As prepared alpha-Ag2S composite NPs were efficiently produced from precursors silver nitrate and sodium sulfite. The extracellular biomolecules produced by Humicola sp. reduced the precursor solution and at the same time it capped the formed Ag2S NPs. The characterization performed by different techniques revealed excellent optical, morphological, and structural properties (size, shape distribution, and crystallinity) of the alpha-Ag2S NPs. The change in color from colorless to dark brown indicated the formation of alpha-Ag2S, which was further confirmed by fluorescence and UV-Visible spectroscopy, showing a sharp peak at 410 nm. Morphological analysis of alpha-Ag2S NPs confirmed the spherical shape, and narrow size distribution. alpha-Ag2S NPs were found to be potent in antimicrobial applications owing to their high dispersibility in water and capping by extracellular biomolecules secreted by Humicola sp. The anti-cancer activity for alpha-Ag2S performed using human breast cancer cell line (ZR-75-1) and human Burkitt's lymphoma cancer (Daudi). The biocompatibility test was performed using human peripheral blood mononuclear cells (PBMCs) for alpha-Ag2S NPs. The anti-leishmania activity was also determined for alpha Ag2S NPs in-vitro using the standard anti-promastigote protocol (Leishmania donovani promastigotes). This extracellular system is an economically and environmentally benign route for the biosynthesis of alpha-Ag2S NPs having desired surface, structure and biomedical properties.
Keywords: Cytotoxicity; Fungus; Hemolysis; Humicolasp; Silver sulfide(alpha-Ag2S)